The civil judge's evidence initiative: An evil debate raised - Picó i Junoy, Joan (2008)
To determine if the judge must or not have probatory initiative, meaning to have appointed proofs by the judge, radical positions must be left aside, this is limitless probatory initiative, or the absolute omission of the appointed proofs by the judge. The point is to look for a balance point where the attribution of the judge of appointed proofs requirement is limited assuring impartiality and protecting the right of defense of the litigants, searching for the respect of the procedural guarantees and also the effectiveness of the process.